Make Capitalism History A Practical Framework for Utopia and the Transformation of Society - Sutterlütti, Simon (Springer Nature, 2023)
This open access book presents an alternative to capitalism and state socialism through the modelling of a post-market and post-state utopia based on an upscaling of the commons, feminist political economy and democratic and council-based planning approaches. It discusses the left's need to explore non-capitalist modes of production, the inability of green or socialist market economies to produce real social and ecological change, and the need to look beyond traditional ideas of reform and revolution. The book discusses how a socio-economic organisation beyond money, wage labour, patriarchal division of work and centralised state planning may look like. It develops an approach to societal transformation based on seed forms of commons practices and social movements. This book will be relevant to activists, students and researchers interested in fundamental social change, political economy and feminist and Marxist economics. This is an open access book.